METODE MOLEKULER UNTUK MENDETEKSI MIKROBA PENYEBAB PENYAKIT PATOGEN - Mustofa, Syazili; Putri Adilla (CV. Jasa Sukses Abadi, 2024)
Pathogenic diseases are diseases that are an important problem for public health, especially in developing countries like Indonesia. This disease occurs when disease-causing microorganisms infect the host's body tissue and then multiply and react to the organism being attacked because of the toxins they produce. Several types of disease pathogens can be caused by viruses, bacteria, fungi and parasites. Detection of pathogenic bacteria as a source of infection still relies on isolation methods in pure media culture and microscopic analysis followed by biochemical reactions. However, when using existing techniques, it is difficult to isolate some bacteria in pure culture media, making it a challenge to develop other methods to identify the source of the infection. So far, identification and detection of pathogenic bacteria has only been carried out by observation based on clinical symptoms and history of disease, as well as morphological and physiological characteristics. However, this method is less efficient so a technique is needed that can detect pathogenic bacteria quickly and accurately. There are several types of methods that can be used to identify pathogenic bacteria, namely, methods that target nucleic acids, immunology-based methods, and biosensor-based methods.